Leverage dan pertumbuhan aset terhadap profitabilitas dan nilai perusahaan - Wahyu Setiyowati, Supami; Dian Indiraswari, Susmita (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This study aims to ascertain how leverage and the expansion of a company's asset base affect profitability and value. Food and beverage companies that are listed on the Indonesia Stock Exchange are the research's target audience. The time frame for the research is 2020–2022. Proportional sampling is the method used for sampling. There are forty companies in the sample. Smart PLS is what we utilize to analyze data. Empirical evidence indicates that a company's value is positively impacted by both growth and leverage. Debt and business expansion have little bearing on profitability. According to the study's findings, a company's assets do not always translate into higher profitability